'fhe importance of humidity in the development and spread of Amblyseius andersoni Chant (Acarina Phytoseiidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
For years it has been known that A. andersoni, taken from the Po Valley (where it has been widespread for some time) to the orchards in the Montpellier area, responded positively in the presence of prey but then declined from June on. The reason for this was sought 1) through laboratory research to determine the humidity needs of this species and 2) by comparing the climatic conditions of the country of origin and that of introduction. The laboratory experiments were carried out by exposing overwintering females in diapause to 50%, 60%, 70%, and 80% RH and temperatures of 20 and 25 °C. It was found that the mortality of the females decreases as the RH increases, that the criticai threshold lies between 70% and 80% RH, and that 80% RH is the optimum level for A. andersoni to live and develop. The comparison between the variations in RH in the Po Valley climate and in that of the Montpellier area shows that in the latter the humidity leve! is lower than in the Po Valley. We can therefore presume that the cause of the failure of A. andersoni to survive in the new habitat is its intolerance to low humidity in certain months of the year, as has been demonstrated for other species. The difficulty in evaluating the actual humidity to which the species is subjected in the climate of the new habitat is discussed.
Keywords: Phytoseiidae; Amblyseius andersoni; humidity; survival